651. Non-encapsulation of Pneumococci as a Potential Evasion Mechanism From Vaccines. (26th November 2018) - Wajima, Takeaki; Ishikawa, Haruna; Suzuki, Shiori; Matsuzawa, Akane; Nakaminami, Hidemasa; Noguchi, Norihisa
Abstract: Background: Our group has been continuously performing epidemiological analyses on capsular types of pneumococci since 2007. Pneumococcal conjugate vaccine decreased the proportion of nonvaccine capsular types. Furthermore, null-capsule isolates that produced PspK were also identified in our analysis. In this study, we analyzed the genetic background of null-capsule pneumococci and the mechanism of nonencapsulation. Methods: Twenty-seven null-capsule isolates from 430 pneumococci that were isolated between 2010 and 2014 were used for this study. The capsular type was identified by DNA sequence-based methods, and genetic backgrounds were compared by multilocus sequence typing. Among the null-capsule isolates, the SP2852 strain was employed for non-encapsulation analysis. The pspK gene of this strain was replaced with ermB by homologous recombination (SP2852 Δ pspK :: ermB ). Then, genomic DNA from SP2852 Δ pspK :: ermB was transformed into encapsulated isolates via natural transformation. Clindamycin-resistant isolates were further analyzed by sequence. Results: The proportion of null-capsule isolates tended to increase from 5% in 2010–2011 to 12.3% in 2014. These null-capsule isolates were classified into 14 STs that included STs previously identified as capsule-positive isolates. To assess non-encapsulation via natural transformation, two encapsulated strains (serotype 19F and 14) were cultured with genomic DNA from SP2852 Δ pspK :: ermB . Subsequently, clindamycin-resistant null-capsule isolates were detected with high frequency (2.5 × 10 –4 –8.7 × 10 –5 ). Sequence analysis showed capsular coding regions of these null-capsule isolates were replaced with that of Δ pspK :: ermB. Furthermore, these isolates grew significant faster than their parent strains. Conclusion: Null-capsule isolates with various genetic backgrounds were revealed gradually after introduction of vaccine. Moreover, encapsulated strains could take up genomic DNA of null-capsule isolates more easily and become a null-capsule strain by homologous recombination, suggesting that non-encapsulation and acquiring PspK resulted in the emergence of null-capsule strains by natural transformation. Furthermore, non-encapsulation could be beneficial for pneumococci as an evasion mechanism from vaccines. Disclosures: All authors: No reported disclosures.